Pengaruh E-Service Quality, Bank Image, dan Ease of Use Aplikasi Mobile Banking terhadap Customer Satisfaction Mobile Banking BCA (Studi Kasus BCA Purwokerto) - Mikhael Adika Daneslan Harefa; Ajeng Aquinia (Economics and Digital Business Review, 2024)
Banking in Indonesia is an industry that is experiencing very rapid development. Therefore, competition in the banking industry will also become increasingly fierce. The banking industry is also expected to be able to seize various existing opportunities and is expected to make a greater contribution to the national economy. Of course, every bank will continue to put forth its best efforts so that it can continue to compete with rival banks. Every bank will of course continue to try to get customers who will buy products and retain their bank customers. Coupled with the development of an increasingly modern era where lifestyle changes have also occurred with a lifestyle that prioritizes technology. This research will focus on testing three independent variables, namely e-service quality, bank image, and ease of use on customer satisfaction. The research method used is a quantitative method using SPSS based on BCA Bank customer respondents located at the Purwokerto City Head Office, Central Java. Based on the results of research conducted, the variables e-service quality and bank image have a significant influence on customer satisfaction. Meanwhile, ease of use does not have a significant influence on customer satisfaction